Antibacterial healing-promoting hydrogel composite dressing and preparation method thereof

By grafting polypolyol acrylate onto POSS molecules and loading antibacterial nanoparticles, a composite dressing of modified POSS material and bacterial cellulose is formed, which solves the problems of existing cellulose hydrogel dressings in terms of antibacterial performance, wound healing promotion and mechanics. performance deficiencies, achieving more efficient antimicrobial, strength and healing-promoting effects.

CN119345445AActive Publication Date: 2025-01-24SHENZHEN LONGGANG DISTRICT NO 2 PEOPLES HOSPITAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411150398.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-24
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing cellulose hydrogel dressings have shortcomings in antibacterial properties, promoting wound healing and mechanical properties, and it is difficult to achieve antibacterial, improving strength and promoting healing simultaneously.

Method used

By grafting polypolyol acrylate onto POSS molecules and loading antibacterial nanoparticles on its surface, a composite dressing of modified POSS material and bacterial cellulose is formed to enhance its antibacterial, mechanical and healing properties.

Benefits of technology

The composite dressing significantly improves antibacterial performance, mechanical strength, and ability to promote healing, which can more effectively relieve patients with patients and accelerate the process of wound recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345445A_ABST
    Figure CN119345445A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medical materials, and particularly relates to an antibacterial healing-promoting hydrogel composite dressing and a preparation method thereof. The composite dressing is obtained by mixing bacterial cellulose and a modified POSS material, the modified POSS material is obtained by initiating reactive groups in POSS molecules to be grafted with polyhydric alcohol acrylate monomers through ultraviolet light and then loading antibacterial nanoparticles on the surfaces of the polyhydric alcohol acrylate monomers. The composite dressing is safe and non-toxic, compared with a traditional hydrogel dressing, the antibacterial property, the mechanical strength and the healing promoting capacity are further improved, the pain feeling of a patient can be better relieved, and the recovery process is accelerated; and the preparation method is simple and controllable, and can be applied to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and particularly relates to an antibacterial and healing-promoting hydrogel composite dressing and a preparation method thereof. Background Art

[0002] Skin wounds caused by diabetes are due to persistent high blood sugar levels and related diabetic complications. Skin wounds caused by diabetes have extremely complex pathology, and their delayed wound healing involves multiple pathophysiological mechanisms, including excessive activation of tissue regional immune response, oxidative stress, reduction of new blood vessels, peripheral neuropathy, imbalance of extracellular matrix accumulation and remodeling, etc. At the molecular level, epigenetic modification, pattern recognition receptor activation, mitochondrial dysfunction and abnormal energy metabolism are all related to delayed healing of diabetic skin wounds.

[0003] Traditional dressings, such as gauze, sterilized cotton wool, and bandages, are the most widely used clinical dressings due to their low cost and simple manufacturing process; they are applied to the surface of skin wounds caused by diabetes to promote wound healing. Although traditional dressings can protect wounds from external infection, they lack controllable wound absorbency and are too dry to cause wounds to heal in time. In addition, in the case of excessive wound drainage, they may adhere to the wound, making it difficult to remove the dressing. Therefore, traditional dressings are usually used for mildly squeezed wounds or as auxiliary dressings.

[0004] Hydrocolloid dressings are medical dressings composed of hydrocolloid molecules with strong water absorption capacity, a gel matrix with adhesive properties, and a semi-permeable protective film. Compared with traditional dressings, hydrogel dressings can keep wounds moist, have better biocompatibility and degradability; they can be replaced or removed without seriously damaging the wound tissue, which is its biggest advantage. In addition, hydrogel dressings are flexible and can fit the wound without squeezing the wound, and can absorb exudate, permeate oxygen and metabolites, and hinder the entry of bacteria. However, traditional gels usually do not have antibacterial activity to prevent bacterial infection of wounds, and hydrogels themselves cannot achieve the effect of promoting wound healing. In addition, traditional hydrogels also have the disadvantages of low strength and poor toughness.

[0005] Bacterial cellulose is a cellulose hydrogel with good biocompatibility synthesized by bacteria. It has a three-dimensional network structure composed of nanofibers, micron-level pores, high porosity and specific surface area, so it has good air permeability and can effectively block bacterial invasion. Compared with traditional hydrogels, bacterial cellulose-based hydrogels have high water content, suitable porosity and good cell compatibility, can provide the required wettability for the wound surface, and can also carry out gas exchange and exudate absorption. Bacterial cellulose-based hydrogels can be conveniently trimmed into any shape, easy to fully contact with the wound site, convenient to wrap and fill the wound, thereby improving the self-healing effect. In addition, the cellulose molecular structure contains a large number of carboxyl groups, which can be combined with hemoglobin iron ions in the blood, thereby activating coagulation factors to promote coagulation, and can promote the adhesion of platelets in the blood, enhancing the hemostatic effect. However, usually a single cellulose-based hydrogel also has the disadvantages of traditional hydrogels, that is, it has no antibacterial activity to prevent wound infection, and the bacterial cellulose hydrogel itself cannot achieve the effect of promoting wound healing. In addition, bacterial cellulose hydrogels also have the disadvantages of low strength and poor toughness. At present, many researchers have tried to solve the shortcomings of cellulose hydrogels, such as insufficient antibacterial properties, inability to promote wound healing, low strength, and poor toughness, by adding antibacterial agents and specific functional materials. However, the current methods for modifying bacterial cellulose hydrogels have relatively single functions and cannot simultaneously provide antibacterial properties, improve hydrogel strength, and promote wound healing. Therefore, it is urgent to develop a multifunctional nano-functional material to improve the various properties of cellulose hydrogels. Summary of the invention

[0006] The purpose of the present invention is to solve the deficiencies of the prior art and further provide an antibacterial and healing-promoting hydrogel composite dressing, which is obtained by mixing bacterial cellulose and modified POSS material; the modified POSS material is obtained by grafting monomers with reactive groups in POSS molecules and then loading antibacterial nanoparticles on the surface; the monomers are polyol acrylates; and the reactive groups are selected from vinyl, acryloxy or acrylic groups.

[0007] The present invention adopts polyol acrylate grafted on POSS molecules (i.e. cage-type polysilsesquioxane), which can give the modified POSS material good water solubility and dispersibility in hydrogel, and reduce agglomeration phenomenon; on the other hand, the terminal hydroxyl group and ether bond in the grafted polyol molecular chain can interact with polar groups such as the side hydroxyl group and carboxyl group of bacterial cellulose to form hydrogen bonds, and the rigid cage structure of POSS also has good modulus and strength, and the two cooperate with each other to achieve the effect of enhancing the mechanical properties of cellulose-based hydrogel. In addition, the grafted polyol molecular chain has good biocompatibility like the POSS molecule, and also has good moisturizing and moisturizing properties, which can provide a moist and cell-friendly microenvironment for the wound surface of diabetic wounds, thereby promoting the wound healing process, reducing scar formation, and effectively relieving the pain of patients; it also has excellent oxygen permeability and antibacterial ability, can effectively prevent wound infection, and further accelerate the wound recovery process. Moreover, since the POSS molecules grafted with polyols have good water solubility and dispersibility, they can be more evenly dispersed in an aqueous solution, which is more conducive to the process of loading antibacterial nanoparticles, thereby giving the modified POSS material of the present invention an antibacterial effect.

[0008] The structural formula of POSS molecule is as follows:

[0009]

[0010] Wherein, R can be independently selected from different groups, including reactive groups and inert groups. In the invention, at least one R needs to be a reactive group, that is, there is at least one reactive group in the POSS molecule used in the present invention to achieve the above effect.

[0011] After research, it was found that the reactive groups can only be vinyl, acryloyloxy or acrylic groups. Only these groups can be polymerized under ultraviolet light conditions and realize the subsequent grafting reaction. In addition, simple polyols cannot directly achieve polymerization grafting under ultraviolet light conditions. Therefore, polyols with acrylate groups must also be used to cooperate with the aforementioned specially selected reactive groups to achieve polymerization grafting under ultraviolet light conditions and realize the grafting of polyol molecular chains onto POSS.

[0012] In some preferred embodiments, the monomer is at least one of polyethylene glycol diacrylate, polypropylene glycol diacrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate and polybutylene glycol diacrylate.

[0013] In some preferred embodiments, the number of the reactive groups is 8. POSS molecules are hybridized into the hydrogel as crosslinking points. When there are more reactive groups in the POSS molecules, multiple reactive groups can be chemically crosslinked. Compared with fewer reactive groups, there are more crosslinking points. Therefore, the crosslinking density is greater at the same content, and the mechanical strength enhancement effect is better.

[0014] In some preferred embodiments, the antibacterial nanoparticles are at least one of nanosilver, nanotitanium dioxide, nanozinc oxide, and nanocopper oxide.

[0015] In some preferred embodiments, the modified POSS material accounts for 10%-40% of the mass of the bacterial cellulose. If the proportion of the modified POSS material is too high, the proportion of the bacterial cellulose will be too low, which will affect the formation of the hydrogel; if the proportion of the modified POSS material is too low, the antibacterial effect, the strength of the hydrogel and the healing effect will be affected to a certain extent.

[0016] The present invention also provides a method for preparing the above-mentioned antibacterial and healing-promoting hydrogel composite dressing, comprising the following steps: mixing the above-mentioned bacterial cellulose and the above-mentioned modified POSS material to obtain the above-mentioned antibacterial and healing-promoting hydrogel composite dressing; wherein the preparation process of the above-mentioned modified POSS material is as follows: under the conditions of ultraviolet light initiator and ultraviolet light, grafting the above-mentioned monomer on the reactive group of the above-mentioned POSS molecule, and then loading the above-mentioned antibacterial nanoparticles on the surface through redox reaction.

[0017] The invention uses ultraviolet light to initiate grafting modification, and the modification method has simple and convenient steps. The length of the grafted polyol molecular chain can be adjusted by changing conditions such as irradiation intensity, irradiation time, monomer concentration, etc., so as to optimize the performance of the modified POSS material.

[0018] In some implementations, the irradiation light source may use a UVLED light source, and the irradiation intensity may be 2000 mW / cm 2 -10000mW / cm 2 , preferably 5000mW / cm 2 , the irradiation time can be 0.5h-6h, preferably 1h. If the irradiation intensity is too strong or the irradiation time is too long, the molecular chain polymerization of the grafted polyol will be too long, which will make it difficult for POSS to modify the loaded antibacterial nanoparticles, and the monomers will be more likely to self-polymerize; if the irradiation intensity is too low or the irradiation time is too short, the molecular chain polymerization reaction of the grafted polyol is insufficient, which will also cause the molecular chain of the POSS grafted polyol to be too short, which is not conducive to the dispersion of POSS in the aqueous solution.

[0019] In some embodiments of the above-mentioned preparation method, the above-mentioned modified POSS material is dispersed in water, and then the above-mentioned bacterial cellulose is added to form the above-mentioned antibacterial and healing-promoting hydrogel composite dressing. Further, after the above-mentioned bacterial cellulose and the above-mentioned modified POSS material are mixed, the obtained hydrogel is freeze-dried. The above-mentioned modified POSS material is still an inorganic material. It is first dispersed in water, so that the grafted polyol molecular chain can be more fully unfolded, and then more fully dispersed in water, and it is more difficult to reunite. If cellulose is added first, it is easy to cause the viscosity of the solution system to increase. At this time, adding the above-mentioned modified POSS material again is not conducive to the above-mentioned modified POSS material being fully dispersed, and it is easy to produce certain reunions, which leads to a decrease in mechanical properties, and the adverse effects such as uneven antibacterial effect.

[0020] In some embodiments of the above-mentioned preparation method, the above-mentioned ultraviolet light initiator is at least one of polyethylene glycol diacrylate, polypropylene glycol diacrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate and polybutylene glycol diacrylate; the amount of the above-mentioned ultraviolet light initiator is 0.5%-5% of the mass of the above-mentioned monomer; the amount of the above-mentioned monomer is 50%-300% of the mass of the above-mentioned POSS molecule.

[0021] The beneficial effects of the present invention are as follows: the composite dressing of the present invention is safe and non-toxic, and compared with traditional hydrogel dressings, further improves the antibacterial performance, mechanical strength and healing ability, can better relieve the patient's pain and accelerate the recovery process; and the preparation method is simple and controllable, and can be mass-produced and applied. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Shown is a scanning electron microscope image of the vinyl POSS molecule in Example 1;

[0023] Figure 2 Shown is a transmission electron micrograph of the modified POSS material in Example 1;

[0024] Figure 3 Shown is a product image of the antibacterial and healing-promoting hydrogel in Example 1;

[0025] Figure 4 Shown is a photograph of an inverted container containing the antibacterial and healing-promoting hydrogel in Example 1;

[0026] Figure 5 Shown is a stress-strain curve graph of the composite dressing;

[0027] Figure 6 Shown is the antibacterial effect of the composite dressing;

[0028] Figure 7 Shown is the live and dead bacteria staining test result of the composite dressing;

[0029] Figure 8 Shown is a graph of wound healing rates for composite dressings. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments and drawings to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.

[0031] The structure of the POSS molecule in the following examples is shown below:

[0032]

[0033] Example 1

[0034] An antibacterial and healing-promoting hydrogel composite dressing, the preparation method of which comprises the following steps:

[0035] (1) Synthesis of modified POSS materials:

[0036] a. Graft modification: 500 mg of vinyl POSS molecules (ie, 8 R groups are vinyl; its scanning electron microscopy image is as follows Figure 1 As shown by Figure 1 It can be seen that pure POSS molecules are mostly in a cubic state) dissolved and dispersed in 20 mL of tetrahydrofuran (THF); it should be noted that, in some other embodiments, chloroform or dichloromethane can be used instead of THF;

[0037] Then, 400 mg of polyethylene glycol diacrylate (monomer) and 10 mg of 1-hydroxycyclohexyl phenyl ketone (ultraviolet light initiator) were added to the above solution and stirred evenly; then the solution was transferred to ultraviolet light irradiation conditions with an irradiation intensity of 3000 mW / cm 2 , irradiated for 3 hours; then washed with THF and DMF in sequence to remove unreacted monomers, centrifuged and dried to obtain a grafted POSS sample;

[0038] b. Load treatment: 200 mg of the grafted POSS sample obtained above was added to 50 mL of silver ammonia solution, ultrasonically dispersed for 10 min, then vigorously stirred at 60 ° C for 1 h (speed of 800 rpm), centrifuged to obtain a modified POSS material loaded with nano-silver particles; its transmission electron microscopy image as Figure 2 As shown by Figure 2 It can be seen that the prepared modified POSS material is in a spherical state, has a core-shell structure, and is loaded or modified with nanosilver particles on the surface.

[0039] (2) Synthesis of antibacterial and healing-promoting hydrogel composite dressing:

[0040] Take 100 mg of the modified POSS material prepared in the above (1), add it to 20 mL of deionized water, stir evenly, heat and maintain it at 50° C., add 1 g of bacterial cellulose to the solution, stir it thoroughly at 800 rpm for 60 min until the solution becomes clear and transparent, and obtain the antibacterial and healing-promoting hydrogel, i.e., cellulose / 10 wt% modified POSS composite dressing; Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the prepared hydrogel has a certain viscosity and does not flow even if the container is inverted. Finally, a freezing treatment is performed, that is, the hydrogel is placed at -20°C for 24 hours and then thawed at room temperature for 4 hours; the freezing treatment is repeated 3 times, freeze-dried, and moisture is removed to obtain the antibacterial and healing-promoting hydrogel composite dressing.

[0041] Example 2

[0042] An antibacterial and healing-promoting hydrogel composite dressing, the preparation method of which is different from that of Example 1 in that the content of the added modified POSS material loaded with nanosilver particles is 20wt% relative to the bacterial cellulose; the rest is the same as that of Example 1.

[0043] Example 3

[0044] An antibacterial and healing-promoting hydrogel composite dressing, the preparation method of which is different from that of Example 1 in that the content of the modified POSS material loaded with nanosilver particles added is 30wt% of the bacterial cellulose; the other steps are the same as those of Example 1

[0045] Comparative Example 1

[0046] A composite dressing, the preparation method of which is different from that of Example 1 in that: there is no grafting modification step, no loading treatment step of loaded nanosilver particles, and the same vinyl POSS molecules (i.e., 8 R groups are all vinyl groups) in Example 1 are directly subjected to step (2) in Example 1; other processes are the same as in Example 1.

[0047] Effect test

[0048] (1) Mechanical testing

[0049] The antibacterial and healing-promoting hydrogel composite dressing prepared in Example 1 (i.e., bacterial cellulose / modified POSS composite dressing), the composite dressing prepared in Comparative Example 1 (i.e., bacterial cellulose / POSS composite dressing), and the pure bacterial cellulose dressing (i.e., the blank control group) were subjected to mechanical testing. The results of the stress-strain curves of the tensile tests are shown in FIG. Figure 5As shown by Figure 5 It can be seen that the composite dressing of the present invention has better strength and elongation at break.

[0050] (2) Antibacterial effect test

[0051] The antibacterial and healing-promoting hydrogel composite dressing prepared in Example 1 (i.e., cellulose / 10wt% modified POSS composite dressing), the antibacterial and healing-promoting hydrogel composite dressing prepared in Example 2 (i.e., cellulose / 20wt% modified POSS composite dressing), the antibacterial and healing-promoting hydrogel composite dressing prepared in Example 3 (i.e., cellulose / 30wt% modified POSS composite dressing), the composite dressing prepared in Comparative Example 1 (i.e., cellulose / 10wt% POSS composite dressing), and the pure bacterial cellulose dressing (i.e., pure cellulose dressing) were subjected to antibacterial performance test and live and dead bacteria staining test.

[0052] Antibacterial performance experiment: Take 1×10 6 150 μL of CFU / mL Escherichia coli suspension was added to the test tube, and 150 μL of Luria-Bertani (LB) liquid culture medium (control group) and the above-mentioned dressings were added at the same time. After thorough mixing, the mixture was co-cultured at 37°C and 100 r / min for 48 h. The absorbance of each group at a wavelength of 600 nm was measured with an enzyme marker at 0 h and 48 h to determine the antibacterial performance.

[0053] Live / dead bacterial staining test: 200 μL of each dressing was added to a 24-well plate and allowed to gel in a 37°C sterile incubator. Then 200 μL of 1.0×10 6 CFU / mL of E. coli suspension were co-cultured at 37°C for 24 hours, and the control group was an E. coli suspension containing LB liquid culture medium. After 24 hours, LIVE / DEADBacLight staining solution (Invitrogen, USA) was added to the experimental group and the control group respectively, and incubated in the dark for 15 minutes. The fluorescence images were observed by laser confocal microscopy, and the fluorescence intensity of dead and live bacteria in each treatment group was calculated.

[0054] The results are as follows Figure 6 and Figure 7 As shown by Figure 6 It can be seen that pure POSS molecules and pure bacterial cellulose hydrogels have no antibacterial effect, while the composite dressing prepared in Example 1 has a good antibacterial rate. When its content is greater than or equal to 20wt%, the antibacterial rate can reach nearly 100%.

[0055] (3) Animal testing

[0056] Animal tests were conducted on the antibacterial healing hydrogel composite dressing (i.e., bacterial cellulose / modified POSS composite dressing) obtained in Example 1, comparative example 1 (i.e., bacterial cellulose / POSS composite dressing), and pure bacterial cellulose dressing (i.e., control group); specifically, after the mice were adaptively fed for 1 week, they were replaced with a high-fat diet (60% fat energy supply) and continued to be fed for 4 weeks. Then, the streptozotocin solution (0.01 mL / g) prepared was injected intraperitoneally for 5 consecutive days, and the fasting and water-free period was 12 hours before each injection; the blood glucose level of fasting mice was measured by tail vein blood sampling for 2 consecutive days on the 6th and 7th days, and mice with blood glucose higher than 11 mm ol / L were selected for inclusion in the experiment. The mice were then randomly divided into 3 groups, 3 in each group, which were the control group (PBS solution) and the composite hydrogels of different groups. After the mice were anesthetized intraperitoneally with 1% sodium pentobarbital, the back was depilated, rinsed with warm saline, wiped dry, disinfected with iodine tincture, and the full-thickness skin with a diameter of about 1 cm was cut off on the back of the mice to prepare a trauma model. 100 μL of E. coli (1×10 6 CFU / mL) was inoculated on the skin wound. One day after infection, 200 μL of the solution of the control group and each experimental group was placed on the back wound. The wound healing area and healing time were observed and recorded on the 0th, 3rd, 7th, 10th and 14th days after the wound. The wound healing rate was calculated according to the following formula, and the wound healing speed was evaluated. Wound healing rate = (initial wound area - wound healing area) / initial wound area × 100%.

[0057] The results are as follows Figure 8 As shown, from Figure 8 It can be seen that after 14 days of treatment, the wound healing effect of the mice using the composite dressing prepared in Example 1 was significantly better than the wound healing effect of the composite dressings prepared in Comparative Example 1 and the control group.

[0058] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. An antibacterial and healing-promoting hydrogel composite dressing, characterized in that: The antibacterial and healing-promoting hydrogel composite dressing is obtained by mixing bacterial cellulose and modified POSS material; the modified POSS material is obtained by grafting monomers with reactive groups in POSS molecules and then loading antibacterial nanoparticles on the surface; the monomer is polyol acrylate; the reactive group is selected from vinyl, acryloxy or acrylic acid.

2. The antibacterial and healing-promoting hydrogel composite dressing according to claim 1, characterized in that: The number of the reactive groups is 8.

3. The antibacterial and healing-promoting hydrogel composite dressing according to claim 1 or 2, characterized in that: The monomer is at least one of polyethylene glycol diacrylate, polypropylene glycol diacrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate and polybutylene glycol diacrylate.

4. The antibacterial and healing-promoting hydrogel composite dressing according to claim 1, characterized in that: The antibacterial nanoparticles are at least one of nano-silver, nano-titanium dioxide, nano-zinc oxide and nano-copper oxide.

5. The antibacterial and healing-promoting hydrogel composite dressing according to claim 1, characterized in that: The modified POSS material accounts for 10%-40% of the mass of the bacterial cellulose.

6. A method for preparing the antibacterial and healing-promoting hydrogel composite dressing according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing the bacterial cellulose and the modified POSS material to obtain the antibacterial and healing-promoting hydrogel composite dressing; The preparation process of the modified POSS material is as follows: under the conditions of ultraviolet light initiator and ultraviolet light, the monomer is grafted on the reactive group of the POSS molecule, and then the antibacterial nanoparticles are loaded on the surface through redox reaction.

7. The preparation method according to claim 6, characterized in that: The modified POSS material is dispersed in water, and then the bacterial cellulose is added and mixed to form the antibacterial and healing-promoting hydrogel composite dressing.

8. The preparation method according to claim 6, characterized in that: The ultraviolet light initiator is at least one of polyethylene glycol diacrylate, polypropylene glycol diacrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate and polybutylene glycol diacrylate; and / or, The amount of the ultraviolet light initiator used is 0.5%-5% of the mass of the monomer.

9. The preparation method according to claim 6, characterized in that: UV light conditions include: irradiation intensity of 2000mW / cm 2 -10000 mW / cm 2 , the irradiation time is 0.5h-6h.

10. The preparation method according to claim 6, characterized in that: The amount of the monomer used is 50%-300% of the mass of the POSS molecule.

Citation Information

Patent Citations

  • Gelatin / carboxymethyl chitosan / POSS (polyhedral oligomeric silsesquioxane) photo-crosslinking hydrogel and preparation method

    CN103739862A

  • Functional cellulose composite and preparation method thereof

    CN106188629A

  • Transparent antibacterial hydrogel dressing as well as preparation method and application thereof

    CN106620832A

  • Chitosan-based antibacterial wound dressing with excellent mechanical properties and antibacterial properties

    CN111973803A